Using causal energy categories to report the distribution of injuries in an active population: An approach used by the U.S. Army. Issue 9 (September 2019) - Hauschild, Veronique D.; Schuh-Renner, Anna; Lee, Terrence; Richardson, Melissa D.; Hauret, Keith; Jones, Bruce H.
Abstract: Objectives: To describe the etiologic distribution of all injuries among U.S. Army Active Duty soldiers by causal energy categories. Design: Retrospective cohort, descriptive analysis. Methods: Injury was defined as the interruption of tissue function caused by an external energy transfer (mechanical, thermal, radiant, nuclear, chemical, or electrical energy). A comprehensive injury matrix standardized categories by causal energies, body locations, and injury types. Categories differentiated acute (ACT) from cumulative micro-traumatic (CMT) overuse injuries, and musculoskeletal injuries (MSKI) from those affecting other or multiple body systems (non-MSKI). International Classification of Diseases (ICD) diagnoses codes were organized into established categories. The matrix was applied to electronic health records for U.S. Army soldiers in 2017. Results: Mechanical energy transfers caused most injuries (97%, n = 809, 914): 76% were CMT overuse and the remaining were ACT (<21%). The majority (83%) were MSKI (71% CMT, 12% ACT). While almost one-half (47%) were to lower extremities (38% CMT, 9% ACT) the most frequently injured anatomical sites were the knee and lower back (16% each, primarily CMT). Conclusions: For the first time all soldiers' injuries have been presented in the same context for consistent comparisons. Findings confirm the vast majority of injuries in this physically-active population are MSKI, and most are CMT MSKI. A very small portion are non-MSKI or injuries caused by non-mechanical energy (e.g., heat- or cold-weather). Most Army injuries are to the lower extremities as a grouped body region, but additional matrix specificity indicates the most injured anatomical locations are the knee, lower back, and shoulder.